Management of perishing implants with abutment screw fracture - A systematic review - Soja Raju; Vivek V Nair; Harsha Kumar Karunakaran; Noxy George Manjuran (Wolters Kluwer Medknow Publications, 2021)
Aim: To systematically review the reported techniques, for evaluating the risk and difficulty encountered in the management of fractured abutment screw in accordance with the location of fracture, and to develop a logical sequence in managing an implant abutment screw fracture. Settings and Design: Systematic review following PRISMA guidelines. Materials and Methods: A systematic search of the PubMed/MEDLINE database for articles published between January 2000 and March 2020 was performed by 2 independent reviewers. Case reports and case series that described the management of fractured implant abutment screw were included. Published articles were qualitatively analyzed employing CARE guidelines and were classified according to the location of screw fracture with respect to implant platform, risk of damage to the implant, and intervention for managing the fractured screw. Statistical Analysis Used: Qualitative analyisis. Results: A total of 28 articles were included in the review. Two of them explained the management of screw fracture at or above the implant platform and required only mild approach with low risk while the others explained the management of screw fracture below the level of implant platform. Among them, 6 were considered mild approach with low risk, 13 moderate approach with moderate risk, and 8 of them severe approach with high risk. Conclusion: Irrespective of the technique, any attempt to retrieve abutment screw fragment poses some risk to the implant which is varying from mild to severe. As the location of fracture is more gingival to the implant platform, difficulty of retrieval as well as risk to the implant increases. The proposed decisionmaking tree will be a useful tool in helping clinicians to manage abutment screw fracture.